Pengembangan Media Flip Card untuk Mata Pelajaran Bahasa Indonesia Materi Kata Kerja di Kelas 2 Sekolah Dasar - Septiani, Ritana; Arini, Novanita Whindi (Jurnal Pendidikan Sultan Agung, 2024)
The purpose of this study was to develop a verb flip card media used in Indonesian language subjects in grade 2. This study used the Research and Development (RnD) method with the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model. The data collection process was carried out through interviews and observations, then data analysis was carried out which included qualitative and quantitative approaches. The results of the media feasibility test showed an average percentage of 90% from media experts, material experts and education experts. Then the results of the small group trial produced an average percentage of 89.2%, while the large group trial reached an average percentage of 90.4% with very feasible qualifications. Then the pre-test test showed an average of 33.48%, then the post-test increased to 56.89%. The results of this study indicate that this verb flip card media is feasible to use for Indonesian language subjects in grade 2 of elementary school. In addition, this media can make learning activities more interesting, creative, and interactive.